A Comparative Study on Axial Coordination and Ligand Binding in Ferric Mini Myoglobin and Horse Heart Myoglobin - De Sanctis, Giampiero (Biophysical Society, 2007)
The absorption and resonance Raman spectra and the azide binding kinetics of ferric horse heart myoglobin (Mb) and mini myoglobin (a chemically truncated form of horse heart Mb containing residues 32–139) have been compared. The steady-state spectra show that an additional six-coordinated low-spin form (not present in entire horse heart Mb, which is purely six-coordinated high spin) predominates in mini Mb. The distal histidine is possibly the sixth ligand in this species. The presence of two species corresponds to a kinetic biphasicity for mini Mb that is not observed for horse heart Mb. Azide binds to horse heart Mb much more slowly than to sperm whale Mb. This difference may result from a sterically hindered distal pocket in horse heart Mb. In both cases, the rate constants level off at high azide concentrations, implying the existence of a rate-limiting step (likely referable to the dissociation of the axial sixth ligand). The faster rate constant of mini Mb is similar to that of sperm whale Mb, whereas the slower one is similar to that of entire horse heart Mb.